Local anesthetics in Dentistry: a literature review (Research, Society and Development, 2022)
Local anesthesia is essential for performing the vast majority of dental procedures. Mortality cases due to local anesthesia are rare. However, cases of morbidity are more common but not always reported. Given the above, this study aimed to review the literature on local anesthetics used in dentistry, highlighting necessary information regarding the choice and amount of anesthetic, preventing the occurrence of complications. For the construction of this work, a bibliographic survey was carried out in the SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect databases, using the Mendeley reference manager. Scientific studies available in the literature report. Standardizing a solution for general use does not always satisfy the clinical needs and well-being of patients, and can even cause serious problems for them. Although all local anesthetics currently used have similar mechanisms of action, they may differ in terms of duration of action, pharmacological effects, metabolism, associated vasoconstrictor, adverse reactions and, therefore, indications. Thus, the professional must choose the anesthetic solution according to the patient and the procedure to be performed. The best treatment for systemic complications arising from local anesthesia is undoubtedly prevention, through a good anamnesis and physical examination, choosing the safest anesthetic salt for each specific case.